[OP.5B.06] CONCENTRIC LEFT VENTRICULAR REMODELING IS ASSOCIATED WITH EARLY ONSET PREECLAMPSIA IN WOMEN WITHOUT PREEXISTENT HYPERTENSION. (September 2017) - Colussi, G.; Catena, C.; Driul, L.; Rossi, A.; Pezzutto, F.; Fagotto, V.; Martorana, L.; Sechi, L.A.
Abstract : Objective: Preeclampsia (PE) is a maternal complication characterized by hypertension and proteinuria that usually occurs after the 20th gestational week and resolves after delivery. PE is associated with persistent cardiac abnormalities and a high cardiovascular risk during the woman life. Early onset PE presenting before the 34th gestational week is a more severe form of disease, but its relevance on cardiac abnormalities in comparison to the forms with later onset is not clear. The aim of this study was to assess cardiac structure and function in women with PE without preexistent hypertension. Design and method: One month after delivery, the clinical and echocardiographic variables of 54 preeclamptic women (age 36 ± 6 y), 39% of which with early PE, was compared with a group of 54 normotensive (age 37 ± 6 y) and 15 hypertensive (age 41 ± 5 y) nonpregnant women who were matched for age and height. Results: Despite comparable antihypertensive treatment, women with early PE had lower 24-hour average systolic and diastolic blood pressure than those with late PE. Left ventricle (LV) relative wall thickness was significantly greater in women with early PE (0.39 ± 0.10) than in those with late PE (0.31 ± 0.07; p < 0.001) and normotensive (0.29 ± 0.05; p < 0.001) women, but not hypertensive women (figure). Women with early and late PE had comparably greater LV mass and worse diastolic function as assessed by the E/A ratio, isovolumic relaxation time, and tissue Doppler imaging, than normotensive woman. No differences in LV systolic function were observed between preeclamptic and normotensive woman. Conclusions: Women with early onset PE have more pronounced LV concentric remodeling than women with late onset PE. This observation could account for the greater cardiovascular risk of these patients and might prompt the use of antihypertensive drugs specifically acting on LV remodeling. Figure. No caption available.